Older adults' experiences of loneliness over the lifecourse: An exploratory study using the BBC loneliness experiment. (September 2022) - Victor, Christina R; Rippon, Isla; Barreto, Manuela; Hammond, Claudia; Qualter, Pamela
Highlights: 71% of older adults who took part in the study had experienced loneliness in previous life stages. 14% of lonely adults had experienced loneliness in all 5 life stages included in our study (from childhood to old age). Loneliness increased with the time older adults spent alone. Abstract: Purpose: : To explore older adults' experiences of loneliness across the lifecourse and the relationship with current loneliness. Methods: : Our sample is 6, 708 people aged 65 years and older, resident in the UK, who participated in the BBC Loneliness Experiment in spring 2018. Loneliness was assessed using the 3 item UCLA Loneliness Scale, using a threshold score of 6+ to define loneliness. Participants were asked if they had experienced loneliness in 5 life-stages ranging from childhood to old age and, if so, at which stage had they experienced loneliness most intensely. Multivariate logistic regression analysis was used to estimate the odds ratios of experiencing loneliness in relation to previous experiences of loneliness and key covariates. Findings: : 41% of participants reported current feelings of loneliness and were more likely than those who did not to spend time alone, have poorer self-rated health, be unmarried, have fewer financial resources, and lower levels of neighbourhood trust. 71% reported they had experienced loneliness at some previous stage in their life, with 26% experiencing it in childhood (5–15 years and 39% as a young adult (16–24 years). Having had three or more prior life stage experiences of loneliness was an independent risk factor for current loneliness. Conclusion: : We highlight the potential importance of examining older adults' experience of loneliness within a lifecourse perspective. We suggest a research agenda that examines the importance of the number and timing of previous loneliness experiences and investigates the strategies used to cope with loneliness across the lifecourse as a pathway to developing more effective and personalised loneliness interventions.